2015
DOI: 10.1039/c4ra16219f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation and toxicity evaluation of diclofenac by nanotubular titanium dioxide–PES membrane in a static and continuous setup

Abstract: Diclofenac is a commonly used anti-inflammatory drug, which has been found in surface waters. TiO2 nanotubes with a polymer microfiltration membrane showed high photocatalytic degradation of diclofenac combined with an excellent membrane performance and long term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…The increase in the pure water ux under UV light is attributed to the effect of photoinduced hydrophilicity, where the UV light activates TiO 2 NPs, which allows more water to pass through the membrane. In contrast, Fischer et al 42 reported around a 30% decrease in pure water ux aer depositing TiO 2 nanotubes on a PES membrane, which could be attributed to a different method of depositing nanotubes on the membrane.…”
Section: Hydrophilicity and Membrane Resistancementioning
confidence: 89%
“…The increase in the pure water ux under UV light is attributed to the effect of photoinduced hydrophilicity, where the UV light activates TiO 2 NPs, which allows more water to pass through the membrane. In contrast, Fischer et al 42 reported around a 30% decrease in pure water ux aer depositing TiO 2 nanotubes on a PES membrane, which could be attributed to a different method of depositing nanotubes on the membrane.…”
Section: Hydrophilicity and Membrane Resistancementioning
confidence: 89%
“…Fundamental characteristics in view of achieving excellent photocatalytic performance are their high surface area/volume ratio, short distance for charge carrier diffusion, and high photon-collection efficiency. Fischer et al [84] prepared nanotubular TiO 2 -PES membranes. The prepared PMs were tested for degrading DCF under UV light.…”
Section: Ti-and Ag-based Photocatalytic Membrane Reactorsmentioning
confidence: 99%
“…For PMRs with photocatalyst blended with the membrane, the photocatalyst is blended into the membrane matrix, reducing the possibility of photocatalyst leaching compared to photocatalytic-coated membranes [35]. Most researchers selected polyvinylidene fluoride (PVDF) polymeric membranes for the photocatalyst entrapment [36][37][38][39][40][41][42][43], while polyethersulfone (PES) [44][45][46], polyacrylonitrile (PAN) [47], cellulose acetate (CA) [48,49], polystyrene (PS) [50] and polysulfone (PSF) [51,52] were also used. For PMRs with free-standing photocatalytic membrane, its production is often performed via the electrochemical anodization of a titanium metallic substrate, followed by the separation of the TiO 2 nanotube film and different annealing treatments [17].…”
Section: Pmrs With Immobilized Photocatalystmentioning
confidence: 99%